"Why Do They Leave for ISIL"?: A Discourse-Analysis of Young Dagestanis' Narratives. Issue 4 (3rd September 2017) - Vasilieva, Nadezhda; Maiboroda, Alina; Yasaveev, Iskender
Abstract : The article presents the results of the study into the rhetoric of youth in Dagestan about those who left for ISIL. The authors reconstruct the everyday discourse of "leaving for ISIL" among the youth in the region, presented by Russian authorities and media as one of the leading regions in terms of the number of ISIL followers. The research focus is not on the public forms of the construction of social problems, but on everyday talk, in particular on the claims made in the course of in-depth interviews. The study is based on the constructionist research program developed by Peter Ibarra and John Kitsuse and focuses on the identification of the discursive means of problematization used by Dagestani youth in relation to "leaving for ISIL" and young people "leaving." The young Dagestanis occasionally use the rhetoric of endangerment, including the metaphor of a "virus." However, the dominant rhetoric is the rhetoric of unreason. The terms used in the description of those who "left for ISIL" correspond to this idiom's vocabulary. The image of manipulation, which is central for the rhetoric of unreason, is detailed by constructing the image of the "recruiter." One of the identified features of the talk of the "leaving for ISIL" was episodic, that is, different from the previous and subsequent phrases and utterances of young people in accordance with the official discourse, supposedly in order to protect themselves from a possible suspicion of sympathy for ISIL. However, the rhetoric of unreason indicates a lack of social distance between young Dagestanis and those who have "left." Informants express regret and sympathy in relation to their families and link "leaving for ISIL" with unemployment. The informants' speech suggest the need for the development of social policy, education, and employment opportunities in Dagestan, rather than the strengthening of repressive measures.